Automatic exposure compensation and subjective image enhancement in the radiographic diagnosis of caries - Neiandro Santos GALVÃO; Eduarda Helena Leandro NASCIMENTO; Hugo GAÊTA-ARAUJO; Deborah Queiroz FREITAS; Francisco HAITER-NETO; Matheus Lima OLIVEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study aims to assess the influence of high-density material on the radiographic diagnosis of proximal caries in digital systems with automatic exposure compensation, and to evaluate the effect of subjective adjustment of brightness and contrast to undertake this diagnostic task. Twenty bitewing radiographs of forty posterior human teeth with non-cavitated carious lesions, confirmed by micro-CT, were obtained with two digital systems. A porcelain-fused-to-metal crown attached to a titanium implant was inserted into the exposed area, and all the radiographs were repeated. Five radiologists assessed the radiographs and diagnosed proximal carious lesions. Afterwards, the observers were asked to adjust image brightness and contrast, based on their subjective perception, and to reassess the images. Thirty percent of each experimental group was reassessed to test intraobserver reproducibility, totaling 208 images per observer. Intraobserver and interobserver agreements ranged from fair to substantial. Sensitivity, specificity, predictive values, and area under the ROC curve were calculated and compared for each radiographic system, using ANOVA (α = 0.05). Overall, presence of high-density material and adjustment of brightness and contrast did not significantly influence the radiographic diagnosis of proximal caries (p ≥ 0.05). Regarding Digora Optime, adjustment of brightness and contrast significantly increased (p < 0.05) the diagnostic accuracy of proximal carious lesions in the presence of high-density material. In conclusion, the presence of high-density material in the X-rayed region does not influence radiographic diagnosis of proximal caries. However, when it is present in the X-rayed area, subjective adjustment of brightness and contrast is recommended for use with the Digora Optime digital system.